Space-time description of dengue epidemic in Cruzeiro, SP, in 2006 and 2011 - Carvalho, Renata Marzzano de[UNESP]; Costa Nascimento, Luiz Fernando (Assoc Médica Brasileira, 2014)
Objective: to identify patterns in the spatial and temporal distribution of cases of dengue fever occurring in the city of Cruzeiro, state of Sao Paulo (SP).Methods: an ecological and exploratory study was undertaken using spatial analysis tools and data from dengue cases obtained on the SinanNet. The analysis was carried out by area, using the IBGE census sector as a unit. The months of March to June 2006 and 2011 were assessed, revealing progress of the disease. TerraView 3.3.1 was used to calculate the Global Moran's I, month to month, and the Kernel estimator.Results: in the year 2006, 691 cases of dengue fever (rate of 864.2 cases/100,000 inhabitants) were georeferenced; and the Moran's I and p-values were significant in the months of April and May (TM = 0.28; p = 0.01; I-M = 0.20; p = 0.01) with higher densities in the central, north, northeast and south regions. In the year 2011, 654 cases of dengue fever (rate of 886.8 cases/100,000 inhabitants) were georeferenced; and the Moran's I and p-values were significant in the months of April and May (I, = 0.28; p = 0.01; I-M = 0.16; p = 0.05) with densities in the same regions as 2006. The Global Moran's I is a global measure of spatial autocorrelation, which indicates the degree of spatial association in the set of information from the product in relation to the average. The I varies between -1 and +1 and can be attributed to a level of significance (p-value). The positive value points to a positive or direct spatial autocorrelation.Conclusion: we were able to identify patterns in the spatial and temporal distribution of dengue cases occurring in the city of Cruzeiro, SP, and locate the census sectors where the outbreak began and how it evolved.

Identificar padrões na distribuição espaço-temporal dos casos de dengue ocorridos no município de Cruzeiro, SP. Métodos: foi desenvolvido um estudo ecológico e exploratório utilizando ferramentas de análise espacial e com dados de casos de dengue obtidos do SinanNet. Foi feita uma análise por área, tomando-se como unidade o setor censitário do Instituto Brasileiro de Geografia e Estatística (IBGE). Foram analisados os meses de março a junho de 2006 e 2011, que mostraram o avanço da doença. Utilizou-se o programa TerraView 3.3.1; foram calculados os índices de Moran global, mês a mês, e o estimador de Kernel. Resultados: no ano de 2006, foram georreferenciados 691 casos de dengue (taxa de 864,2 casos/100 mil hab.); os índices de Moran e p-valores foram significativos nos meses de abril e maio (IM = 0,28, p=0,01; IM = 0,20, p=0,01) com densidades maiores nas regiões central, norte, nordeste e sul. Em 2011, foram geocodificados 654 casos (886,8 casos/100 mil hab.); os índices de Moran e p-valores foram significativos nos meses de março e abril (IM = 0,28, p=0,01; IM = 0,16, p=0,05) com densidades nas mesmas regiões de 2006. O índice de Moran global (IM) é uma medida global de autocorrelação espacial, que indica o grau de associação espacial no conjunto de informações a partir do produto em relação à média. O IM varia entre -1 e +1, e a ele pode ser atribuído um nível de significância (p-valor). O valor positivo aponta para uma autocorrelação espacial positiva ou direta. Conclusão: foi possível identificar padrões na distribuição espaço-temporal dos casos de dengue ocorridos no município de Cruzeiro, SP, e localizar os setores censitários onde a epidemia teve início e como evoluiu.
Descrição espaço-temporal das epidemias de dengue em Cruzeiro, SP, em 2006 e 2011
Keywords: Dengue; Geographic information systems; Epidemiological surveillance; Ecological study; Spatial distribution of the population; Dengue; Sistemas de informação geográfica; Vigilância epidemiológica; Estudo ecológico; Distribuição espacial da população